Infrastructure and Industrial Development: Bridging the Rural-Urban Divide in Maharashtra with a Focus on Transportation Infrastructure and Industrial Clusters (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Maharashtra, one of India's most economically advanced and industrially progressive states, plays a pivotal role in the nation’s development. However, beneath this industrial prowess lies a stark contrast between the urbanized centers such as Mumbai, Pune, and Nagpur and the rural hinterlands that still grapple with inadequate infrastructure and limited economic opportunities. This research paper seeks to explore the extent to which transportation infrastructure and industrial cluster development contribute to bridging the persistent rural-urban divide within the state. The study focuses on the interlinkages between physical connectivity and economic decentralization, assessing how roadways, railways, freight corridors, and emerging infrastructure projects like the Mumbai-Nagpur Samruddhi Mahamarg and the Delhi-Mumbai Industrial Corridor (DMIC) influence regional development. Furthermore, the research investigates the implementation and impact of state and central industrial policies, special economic zones (SEZs), and MIDC (Maharashtra Industrial Development Corporation) initiatives in promoting equitable growth. By relying primarily on secondary data sources such as government reports, policy documents, development plans, and economic surveys, the paper offers a critical analysis of the current infrastructure and industrial development efforts. It also evaluates how these strategies contribute to reducing spatial inequalities, generating employment, improving rural accessibility, and promoting balanced regional industrialization. Ultimately, this study aims to provide actionable insights and policy recommendations to enhance inclusive development and reduce the socio-economic gap between Maharashtra's urban and rural populations, ensuring that the benefits of industrial growth and connectivity are more evenly distributed across the state.